Chronic khat consumption and its effect on ovarian structure in mice and their offspring - AlBadri, Cinaria; Al-Ani, Imad Matloub Dally; Hiba, Hassan (Department of Anatomy, National University of Singapore, 2014)
Khat is considered a psychoactive drug and has many side effects on different parts of the body organs. In this study the effects of khat on ovarian structure in parental mice and their offspring were investigated. Twelve male and twelve female mice were given orally a dose of 50mg/kg body weight of khat extract by gastric gavage for 4 and 8 weeks. After four weeks of treatment, the male and female mice were allowed to mate. Khat treatment continued for the male mice and for the female mice during pregnancy and after giving birth to their offsprings up to 8 weeks. Adult offspring and their parent were killed at the 4th and 8th weeks of treatment. Histological examination of the ovaries showed many corpus luteum and developing Graafi an follicles with mononuclear infi ltration.